Should I See You Again Soon? Multispecialty Assessment of Impact and Burden of Preoperative History and Physical Update Visits - Soegaard Ballester, Jacqueline M; Ginzberg, Sara P; Finn, Caitlin B; Passman, Jesse; Miranda, Stephen P; Blue, Rachel; Stein, Jacob; Mahmoud, Najjia N; Kelz, Rachel R; Wachtel, Heather (Journal of the American College of Surgeons, 2024)
Federal regulations require a history and physical (H&P) update performed 30 days or less before a planned procedure. We evaluated the use and burdens of H&P update visits by determining impact on operative management, suitability for telehealth, and visit time and travel burden. We identified H&P update visits performed in our health system during 2019 for 8 surgical specialties. As available, up to 50 visits per specialty were randomly selected. Primary outcomes were interval changes in history, examination, or operative plan between the initial and updated H&P notes, and visit suitability for telehealth, as determined by 2 independent physician reviewers. Clinic time was captured, and round-trip driving time and distance between patients' home and clinic ZIP codes were estimated. We identified 8,683 visits and 362 were randomly selected for review. Documented changes were most commonly identified in histories (60.8%), but rarely in physical examinations (11.9%) and operative plans (11.6%). Of 362 visits, 359 (99.2%) visits were considered suitable for telehealth. Median clinic time was 52 minutes (interquartile range 33.8 to 78), driving time was 55.6 minutes (interquartile range 35.5 to 85.5), and driving distance was 20.2 miles (interquartile range 8.5 to 38.4). At the health system level, patients spent an estimated aggregate 7,000 hours (including 4,046 hours of waiting room and travel time) and drove 142,273 miles to attend in-person H&P update visits in 2019. Given their minimal impact on operative management, regulatory requirements for in-person H&P updates should be reconsidered. Flexibility in update timing and modality might help defray the substantial burdens these visits impose on patients.